Batik Fractal: Marriage of Art and Science - Yun Hariadi; Muhamad Lukman; Achmad Haldani Destiarmand (Journal of Visual Art and Design, 2013)
By applying Fourier Transformation, this paper shows that batik has fractal characteristic. This character is shown in batik's fractal dimension between 1 and 2. The isen process in batik is one factor that contributes to create self affine as one of fractal's important characteristic. Anova Test for fractal dimension in this method classifies batik according to patterns and its region. Fractal in batik shows the presence of complexity in traditional art. This complexity arises because the effort to obey pakem rule and media. Furthermore, the presence of fractal in batik becomes the foundation of this paper to create algorithm which will produce new kind of patterns: Batik Fractal. The method used for creating the pattern is L-System and Fractal Dimension. L-System is used to create pattern, while Fractal Dimension is used as a measurement tool for Batik Fractal to compare with traditional batik. Algorithm to create Batik Fractal has been developed into a software known as jBatik. As a software, jBatik becomes a helping tool for batik makers to create new patterns. jBatik v 2.0 has been used as a tool to create new batik patterns in creative industry by involving several batik makers.